Problems of learning to Write Arabic for Eighth Graders at Islamic Junior High School Muhammadiyyah 48 Cikupa Tangerang - Wijaya, Anggraeni Cipta; Aman, Moh (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2024)
AbstractThe purpose of this study was to find out the problems faced by eighth grade students at at Islamic Junior High School Muhammadiyah 48 Cikupa Tangerang related to learning to write Arabic and the teacher's efforts to overcome them.. The research method uses qualitative methods with descriptive analysis (analytic descriptive). While data collection techniques in the form of observation, interviews, questionnaires (questionnaire) and documentation. The results of this study concluded that there are two problematic aspects of learning to write Arabic, namely linguistic aspects and non-linguistic aspects. As for the linguistic aspect, there are two factors, namely the slowness of students in writing Arabic texts, and the lack of students in understanding and distinguishing hijaiyyah letters that can be connected or not. While on the non-linguistic aspect there are two factors, namely the differences in student backgrounds, and the lack of students practicing Arabic. Therefore, the Arabic teacher seeks to overcome the problems that occur, namely: (1) The teacher holds additional classes on learning Arabic, especially writing Arabic; (2) Teachers provide motivation and appreciation of students; (3) The teacher organizes extracurricular activities with Arabic themes. Keywords: Learning Problems, Arabic Language, Arabic Writing.